ANALISIS LINGKUNGAN KERJA DALAM MENINGKATKAN KINERJA KARYAWAN PADA KANTOR KELURAHAN KAYUMANIS KOTA BOGOR - Teguh Firmansyah; Syarifah Ida Farida (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study, entitled “Work Environment Analysis in Improving Employee Performance at the Kayumanis Sub-district Office, Bogor City”, aims to analyze the physical work environment conditions at the Kayumanis Sub-district Office and their role in supporting employee performance improvement. The research focuses on several indicators, namely lighting, temperature and air circulation, workspace layout, color scheme, noise levels, and available work facilities. The method applied is descriptive qualitative, with data collected through observation, interviews, and documentation. The informants consisted of the sub-district head, secretary, section heads, and staff. The findings reveal that, overall, the work environment at the Kayumanis Sub-district Office is fairly supportive of employee activities, although some shortcomings remain. Lighting and color schemes are considered adequate, but temperature and ventilation are not optimal, especially during the daytime due to limited air conditioning. The workspace layout is relatively sufficient, Noise from traffic is present but still tolerable, while work facilities are partly adequate yet still require improvements and additions, particularly in terms of technological equipment and air conditioning. It can be concluded that the physical work environment has an important influence on employee productivity and comfort. Therefore, improvements in temperature control, ventilation, supporting facilities, and workspace arrangements are necessary to further optimize employee performance in providing public services.